Daily Routine in Cosmetic Dermatology - Issa, Maria Claudia Almeida; Tamura, Bhertha (Clinical Approaches and Procedures in Cosmetic Dermatology,, 2017)
The series "Clinical Approaches and Procedures in Cosmetic Dermatology" intends to be a practical guide in Cosmetic Dermatology. Procedures in cosmetic dermatology are very popular and useful in medicine, indicated to complement topical and oral treatments not only for photodamaged skin but also for other dermatosis such as acne, rosacea, scars, etc. Also, full-face treatments using peelings, lasers, fillers and toxins are increasingly being used, successfully substituting or postponing the need for plastic surgeries. Altogether, these techniques not only provide immediate results but also help patients to sustain long-term benefits, both preventing/treating dermatological diseases and maintaining a healthy and youthful skin. Throughout this series, different treatments in Cosmetic Dermatology will be discussed in detail covering the use of many pharmacological groups of cosmeceuticals, the new advances in nutraceuticals and emerging technologies and procedures. This volume, entitled "Daily Routine in Cosmetic Dermatology" will be an important tool for aesthetic doctors, practicing dermatologists, plastic surgeons, and all other physicians interested in the field of aesthetic medicine. It discloses in detail the semiology and general treatments in cosmetic dermatology, providing the state-of-the-art regarding patients' evaluation, photoprotection, nutraceuticals and cosmeceuticals and special prescriptions. Also check the other volumes: Volume II - Chemical and Physical Peelings Volume III - Lasers, Lights and Other Technologies Volume IV - Botulinum Toxins, Fillers and Related Substances.- Resumé vydavatel